MODEL KURIKULUM PENDIDIKAN ISLAM MULTIKULTURAL DI PONDOK PESANTREN MODERN ISLAM ASSALAM SURAKARTA - Abdullah Aly (Jurnal VARIDIKA, 2012)
This research aims to: (1) investigate the curriculum planning of Assalaam Modern Islamic Boarding School Surakarta (henceforth MIBS) and its multicultural values; (2) understand the implementation of Assalaam MIBS curriculum and its multicultural values; (3) reveal the curriculum evaluation of  Assalaam MIBS and its multicultural values; and (4) search a model of curriculum development for multicultural Islamic Boarding Schools. This research produces 4 find- ings. First, closely investigated from multicultural perspectives, the curriculum planning of Assalaam  MIBS  includes  both  multicultural  values  (democratic  and  justice  values)  and  antimulticultural values (discrimination and injustice values). Second, in the curriculum implementation, both multicultural and antimulticultural values are exposed to students. While the values of democracy, solidarity, togetherness, love, forgiveness, peace and tolerance are embedded in the learning materials, activities, and evaluation, the values of discrimination and injustice are found in the learning references, available only for special service program as opposed to regular programs. Third, the curriculum evaluation contains multicultural values such as democracy, peace, tolerance, and togetherness particularly embedded in the processes and product of curriculum evaluation. On the other hand, conflict, hegemony and domination values are found in the interac- tion among students in daily school environments. Fourth, the model curriculum of multicultural Islamic Boarding School needs to consider three aspects: (1) the planning of the multicultural Islamic boarding school curriculum is determined by its process and product; (2) the implementation of the multicultural Islamic Boarding school curriculum is determined by the textbooks that contain multicultural values; learning strategies that stimulate students’ active participation in democratic and interesting learning activities; and evaluation of contextual and comprehensive learning results by making use of oral and written tests, portfolios, and assignments; and (3) the evaluation of the multicultural Islamic Boarding School curriculum is determined by its process and product.